Systematic Literature Review Of Creative Thinking For Primary School Students: Trends, Influencing Factors, And Assessment Instruments - Nata, Andra; Somantri, Mubarok (International Conference on Elementary Education, 2025)
Creative thinking is a 21st-century skill that enables individuals to generate original ideas and innovative solutions. This study used a Systematic Literature Review (SLR) based on PRISMA 2020 of 25 articles published between 2021 and 2025 to identify elementary school students' creative thinking abilities, influencing factors, assessment instruments, and research trends. The results show that students' creative abilities are generally analyzed through four dimensions, ranging from fluency, flexibility, originality, and elaboration, using instruments such as open-ended tests, observation rubrics, or product assessments. The most influential factors include teacher facilitation and feedback, the learning environment, motivation, and student interest, while problem-based and project-based learning are the most dominant and consistently effective approaches. Research trends for 2021–2025 indicate an increase in quasi-experimental studies on learning models and the development of assessment instruments and learning media. These findings emphasize the need for more contextual and innovative learning designs, validated multimodal assessment instruments, and research with stronger designs and representative samples to improve the generalization of results